PENGUATAN KEWIRAUSAHAAN LINTAS BUDAYA MELALUI WORKSHOP PEMBUATAN MOCHI KOPI BERBASIS KOPI GAYO BAGI PESERTA SUMMER CAMP THAILAND - Syafridha Yanti; Sulistio Ningsih; Zainal Abidin; Rizky Bintang Setiawan; Tias Sil Romansyah; Iskandar; Evi Lestaria; Nopri Abadi miko; Arda tonara; Ashari Efendi; M Khoiri (LPPI UMN AL WASHLIYAH, 2026)
The Summer Camp program serves as a cross-cultural learning platform that enables international participants to explore local resources while developing entrepreneurial competencies. However, most participants had limited knowledge of Gayo Coffee as Aceh's leading commodity and its potential for product diversification as a creative business opportunity. This community service program aimed to strengthen the cross-cultural entrepreneurial competencies of Thailand Summer Camp participants through a workshop on producing Gayo Coffee-based mochi. The program employed Participatory Learning and Experiential Learning approaches, including lectures, demonstrations, hands-on group practice, discussions, and evaluation sessions. The results indicated that participants improved their understanding of the characteristics and economic value of Gayo Coffee, acquired practical skills in producing coffee mochi, and enhanced their ability to collaborate within multicultural teams. In addition to improving entrepreneurial knowledge and practical skills, the workshop broadened participants' perspectives on utilizing local resources as innovative and value-added products with entrepreneurial potential. Therefore, the Gayo Coffee-based mochi workshop can serve as an effective learning medium for strengthening cross-cultural entrepreneurship while promoting Aceh's flagship local product to the international community.